Pengaruh Waktu Perendaman Zat Warna Poli Kuersetin terhadap Efisiensi Dye Sensitized Solar Cell (DSSC) - Putri, Tiara Dwi; Hardeli, Hardeli (Journal of Natural Sciences, 2024)
The demand for electricity in Indonesia will continue to increase. This condition requires an increase in electricity production capacity from new and renewable energy (NRE) sources. The rising demand for electrical energy leads to the depletion of non-renewable natural resources, driving the shift towards renewable resources such as solar energy. Solar energy can be converted into electrical energy known as solar cells. Third-generation solar cells, known as dye-sensitized solar cells (DSSCs), have the ability to generate electrical energy using organic materials. The objective of this research is to improve the efficiency of DSSCs by using polymerized dyes and doping the TiO2 semiconductor with the surfactant CTAB using the sonication method. This research was conducted to achieve optimum efficiency with variations in the dye immersion time in the polyquercetin solution, specifically 10, 20, 30, 40, and 50 minutes. Characterization using UV-DRS was performed to observe the band gap energy of the semiconductor. The results of the study showed that the DSSC tested for current and voltage with a digital multimeter yielded the lowest efficiency of 7.9% with a 10-minute immersion time and an optimum efficiency of 19.3% with a 30-minute immersion time.